A TV DIGITAL DIVULGADA NO BOLETIM ELETRÔNICO DO FNDC: UM ESTUDO SOBRE O COMPORTAMENTO DA MÍDIA NA IMPLANTAÇÃO DA TV DIGITAL NO BRASIL - Pacheco, Roni Petterson de Miranda (2009)
Even though it has been implemented in Brazil in the 50's, the Television considered the most comprehensive and ideologically sweeping media among its public - faces its second major transformation: from an analog to a digital communication tool. That fact brings to light the new reception possibilities and the convergence of media. In this context, the objective of this study was to analyze the SBTVD-t s (Brazilian System of Digital Terrestrial Television) process of installation by using some online editions from the FNDC s (National Forum for Democratization of Communication) clipping. The analysis of that material concerned the investigation of tendentious characters in the FNDC s published material, which was geared to the technical aspects of the new technology rather than its social potential. Thus, a quantitative research technique basis was chosen to provide the information found in this thesis, leading to the finding that FNDC appears inefficiently when it comes to its critical posture facing the great media. It also showed that some of FNDC s goals weren t met since that forum only reproduces discourses and ideas from other communication vehicles. Similarly, it was found that the Brazilian Government didn t meet its SBTVD decrees either.(AU)